A chemical investigation of the essential oil of Eugenia caryophyllus (Sprengel) Bullock et Harrison (Family Myrtaceae) - Egbuji, John Obiora
The dried flower buds of Eugenia caryophyllus (Sprengel) Bullock et Harrison (formely Eugenia caryophyllata Thunberg) (Family Myrtaceae), were extracted by steam distillation, using the Clevenger apparatus for oils heavier than water. An almost colorless oil was obtained. The yield of the essential oil was 13.6%.